A Contribution to the Empirics of Economic and Human Development - Sebastian Vollmer (Peter Lang International Academic Publishers, 2009)
This book contributes to the empirical literature on economic and human development from five different perspectives: the first chapter provides a new statistical test for bimodality of densities with an application to income data. The second chapter analyzes the worlds cross-country distribution of income and challenges the so called Twin Peaks-claim. The third chapter focuses on the world income distribution and resulting implications for poverty reduction, pro-poor growth and the evolution of global inequality. The fourth chapter estimates the welfare effects of recently negotiated Economic Partnership Agreements between the EU and African countries. Finally, the fifth chapter investigates whether democracy leads to higher levels of health and education.
Keywords: 330